Mechanical and thermal properties of polylactide/talc microcomposites: before and after accelerated weathering. (18th November 2015) - Kaynak, Cevdet; Erdogan, Ali Riza
Abstract : The purpose of the first part of this study was to investigate effects of micron‐sized talc content on the properties of polylactide (PLA). PLA/talc microcomposites were compounded by melt‐mixing method via twin‐screw extruder, while specimens for testing and analyses were shaped by injection molding. It was observed that, because of the effective stiffening, strengthening, toughening mechanisms of talc, and also their nucleation agent effects for higher crystallinity, many mechanical and thermal properties were improved. In the second part of the study, effects of accelerated weathering on the behavior of PLA microcomposites with 5 wt% talc were investigated by applying ultra violet irradiation and humidity steps according to Cycle‐C of International Organization for Standardization 4892‐3 standards for durations of 100, 200, and 300 hr. Various analyses revealed that, because of the degradation mechanisms of photolysis and hydrolysis during each weathering periods, molecular weight of PLA reduced drastically, that is, mechanical properties almost vanished. Copyright © 2015 John Wiley & Sons, Ltd.